The Customer Satisfaction Roles in Customer Satisfaction Affect the Quality of Service Customer Loyalty - Sihombing, Ati Fitriani; Meitiana, Meitiana (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
Customer loyalty is a very important aspect, and therefore, efforts are needed to increase customer loyalty by using several supporting factors, such as improving service quality so that customers are satisfied. This study aims to determine the effect of service quality on customer loyalty mediated by customer satisfaction. This research is quantitative. The sample obtained in this study was selected using simple random sampling. The number of samples used in this study was 78. The data analysis method used was the Partial Least Square (PLS) approach. The results of the study indicate that hypothesis 1 is significant, with a t-statistic value of 37.397 > 1.96 and a p-value of 0.000 < 0.05. This result proves that service quality plays a role in creating customer satisfaction and increasing customer loyalty. Hypothesis 2 is significant, with a t-statistic value of 23.791 > 1.96 and a p-value of 0.000 < 0.05. This result proves that service quality has a role in creating customer satisfaction and increasing customer loyalty. Hypothesis 3 is significant with a t-statistic value of 8.002 > 1.96 and a p-value of 0.000 < 0.05. This result proves that customer satisfaction is important in increasing customers' loyalty at Café Bandrek Opung Palangkaraya.